Noise, sources of noise and its influence on the quality of work and living environment - Korica, Sanja Lj.; Popović, Kristina D. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Fast technological development has made noise an inevitable part of everyday life. The main sources of noise are: machines, factories, traffic and noise from the neighbourhood. As a mixture of sounds of different charcteristics, noise can be permanent, nonpermanent and impact with different levels, duration and time distribution. Due to the harmful effects of noise on human health, it is necessary to undertake steps which will conrtribute to the reduction of noise levels. Noise pollution and activities for the protection against noise have been analysed in this paper.
Keywords: acoustics; noise